New Insights Into the Roles of Microglial Regulation in Brain Plasticity-Dependent Stroke Recovery - Yu, Fang; Huang, Tingting; Ran, Yuanyuan; Li, Da; Ye, Lin; Tian, Guiqin; Xi, Jianing; Liu, Zongjian (Frontiers in Cellular Neuroscience, 2021)
Stroke remains the leading cause of long-term disability worldwide with significant long-term sequelae. However, there is no highly effective treatment to enhance post-stroke recovery despite extensive efforts in exploring rehabilitative therapies. Neurorehabilitation is recognized as the cornerstone of functional restoration therapy in stroke, where treatments are focused on neuroplastic regulation to reverse neural structural disruption and improve neurofunctional networks. Post-stroke neuroplasticity changes begin within hours of symptom onset and reaches a plateau by 3 to 4 weeks within the global brain in animal studies. It plays a determining role in spontaneous stroke recovery. Microglia are immediately activated following cerebral ischemia, which has been found both proximal to the primary ischemic injury and at the remote brain regions which have functional connections to the primary injury area. Microglia exhibit different activation profiles based on the microenvironment and adaptively switch their phenotypes in a spatiotemporal manner in response to brain injuries. Microglial activation coincides with neuroplasticity after stroke, which provides the fundamental base for the microglia-mediated inflammatory responses involved in the entire neural network rewiring and brain repair. Microglial activation exerts important effects on spontaneous recovery after stroke, including structural and functional reestablishment of neurovascular networks, neurogenesis, axonal remodeling, and blood vessel regeneration. In this review, we focus on the crosstalk between microglial activation and endogenous neuroplasticity, with a special focus on the plastic alterations in the whole brain network and their implications for structural and functional restoration after stroke. We then summarize recent advances in the impacts of microglial phenotype polarization on brain plasticity, trying to discuss the potential efficacy of microglia-based extrinsic restorative interventions in promoting post-stroke recovery.